Knowledge of COVID-19 among Brazilian health care professionals and associated factors - Bernardes, João Marcos [UNESP] (2022)
Health care professional's knowledge is essential to contain epidemics. This research aimed to evaluate the knowledge of Brazilian health care professionals regarding COVID-19 to analyze whether there is a difference in knowledge between professionals in Primary Health Care and those in other levels of care or not; and to identify factors associated with knowledge. This is a cross-sectional study, including 716 participants who answered an online questionnaire between April and May 2020. Descriptive statistics, difference tests between groups, and logistic regression models were used to analyze the data. The average knowledge score was 12.42 points (out of a possible total of 15). There was no significant difference between professionals in Primary Health Care and those in other levels of care. Knowledge was associated with age, profession, perception regarding media's information quality, and hours exposed to information on COVID-19. Participants showed adequate knowledge, despite some specific gaps. Continuing education actions should prioritize younger nonmedical professionals.